Pengaruh Efektivitas Pelayanan Pendaftaran Online Aplikasi Mobile JKN Terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit Karya Bhakti Pratiwi Bogor - Yunengsih, Yuyun; Elvin, Febri Gesta (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Digital transformation in healthcare services is an essential requirement for enhancing efficiency and patient convenience. This study aims to analyze the influence of the effectiveness of online registration services through the Mobile JKN application on patient satisfaction at Karya Bhakti Pratiwi Hospital in Bogor. The research employed a quantitative approach with a causal associative design involving a survey of 100 outpatient respondents and supporting data from interviews obtained from the period of February 10 to May 10, 2025. The findings indicate that service speed and ease of access are the most important aspects for patients. Factors such as digital literacy, internet network quality, user experience with the application, and staff support significantly contribute to service effectiveness. The effectiveness of the service has been proven to have a significant positive impact on patient satisfaction. Nevertheless, several issues were identified in its implementation, such as discrepancies in real-time information displayed by the application, limited patient understanding of features and registration steps, and an application flow that is not fully understood by some users. Therefore, it is recommended that hospitals emphasize strengthening patients' digital capabilities, improving service infrastructure, and providing staff support to ensure the success of a more inclusive, adaptive, and patient-centered digital healthcare transformation.